UPAYA PENURUNAN TINGKAT FATALITAS TITIK RAWAN KECELAKAAN DI KABUPATEN GUNUNG KIDUL DAERAH ISTIMEWA YOGYAKARTA - Nohan Rudrokasworo, Silvanus; Tjahjono, Tri; Taufik Mulyono, Agus (Jurnal Transportasi, 2009)
Fatality level can be reduced with the deficiency safety program as an effort in handling the accident thatoccurred on the road. This study aims to investigate the influence of the road infrastructure condition and toassess the best solution to minimize the probability of the accident. The parameter used to determine thelocation of the study was based on AEKâs value, fatalityâs level, and accident frequency. This study wascarried out in the black spot at Yogyakarta â Wonosari road, that were: (1) Bunder (KM 10+944 m); (2)Pekerjaan Umumtat (KM 7+864 m); and (3) Patuk (KM 0+874 m). This analysis was perfomed using the IKJwith measuring design deviation (geometric and roadâs facilities harmonization) toward technical standard.Infrastructure improvements should be conducted to conform components based on the risk analysis.Handling priority of deficiency road infrastructure in the black spot should be based on: (1) traffic handling;(2) harmonization of fringe and mark; and (3) arrangement of roadâs facilities.Keywords: black spot, deficiency, fatality, IKJ, risk analysis